2017
DOI: 10.1504/ijlic.2017.080645
|View full text |Cite
|
Sign up to set email alerts
|

Intellectual capital and firm performance in India: a comparative study between original and modified value added intellectual coefficient model

Abstract: Abstract:With the dawn of a knowledge economy, the role of intellectual capital in value creation and sustainable competitive advantage became evident. With increasing importance of intellectual capital, the emphasis on its management and measurement increased manifolds. The Pulic's value added intellectual coefficient (VAIC) model is one such method that has been widely used for measuring intellectual capital and examining the link between IC and firm performance. However, this model has been criticised becau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
33
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 17 publications
5
33
0
5
Order By: Relevance
“…This model added the third component of IC, relational capital (RC), measured with marketing costs (Nazari and Herremans, 2007). The latest study by Maji and Goswami (2017) showed that the MVAIC model to some extent captures the structural capital efficiency (SCE) of a firm more efficiently than the original model (VAIC).…”
Section: Introductionmentioning
confidence: 99%
“…This model added the third component of IC, relational capital (RC), measured with marketing costs (Nazari and Herremans, 2007). The latest study by Maji and Goswami (2017) showed that the MVAIC model to some extent captures the structural capital efficiency (SCE) of a firm more efficiently than the original model (VAIC).…”
Section: Introductionmentioning
confidence: 99%
“…Celem niniejszego opracowania jest weryfikacja efektywności kapitału intelektualnego oraz jego wpływu na wyniki finansowe badanej jednostki. Do badania wykorzystano zmodyfikowany wskaźnik intelektualnej wartości dodanej (MVAIC) [Ulum 2015;Maji, Goswami 2017]. Model ten uwzględnia dodatkowy kom-ponent kapitału intelektualnego -kapitał relacji, mierzony nakładami na badania i rozwój oraz kosztami marketingowymi jednostki, a także przekształcony wskaźnik efektywności kapitału strukturalnego (SCE -Structural Capital Efficiency).…”
Section: Wstępunclassified
“…Według nich na umiejętność organizacji do tworzenia wartości wpływa zdolność wprowadzania innowacji w produktach, procesach czy technice, które to w znacznym stopniu uzależnione są z kolei od inwestycji jednostki w badania i rozwój. W tworzeniu wartości uczestniczą także relacje z kontrahentami organizacji i innymi zainteresowanymi stronami [Maji, Goswami 2017].…”
Section: Wstępunclassified
See 1 more Smart Citation
“…Zéghal & Maaloul (2010) and Nimtrakoon (2015) found that intellectual capital has a positive effect on financial perfor-mance in the listing company in United Kingdom, Indonesia, Malaysia, Philippines, Singapore, and Thailand. Nimtrakoon (2015) also found that intellectual capital has a positive effect on market performance and it is supported by Amin et al (2014), Hejazi, Ghanbari, & Alipour (2016), Nadeem, Gan, & Nguyen (2018), and Maji & Goswami (2017). On the contrary, Ozkan, Cakan, & Kayacan (2017) found that intellectual capital does not affect financial performance.…”
Section: Introductionmentioning
confidence: 98%